Using Scrabble In Developing The Vocabulary Mastery Of The Seventh Grade Students Of SMPN 3 Parepare - Rina Anggreni Putri; Patahuddin; Ika Yanti Ziska (La Parole : Journal of Language Teaching and Pedagogy, 2020)
This study aim to train students' vocabulary abilities using scrabble. Based on the data from the observations of the researcher through the student's vocabulary knowledge test, the students' ability was still classified as low before got treatment. This is caused by the teacher's media which makes students less interested in the English learning process. So the researchers tried to improve students' vocabulary skills by using the Scrabble game in seventh grade students at SMPN 3 Parepare. The researcher used a quasi-experimental design. The population was 60 students consisting of 30 students each class at SMPN 3 Parepare. Class VII.5 as the experimental class and class VII.4 as the control class. Researcher using random sampling in took sampling in this research. Then the researchers used the pre-test and post-test for data collection. The results of the data analysis showed that the students' vocabulary knowledge skills increased in the learning process using the Scrabble game. This is indicated by the difference between the students' mean score in the experimental class in the pre-test (54.08) post-test (77.78) and the control class in the pre-test (47.31) post-test (62.3) while the value difference distance is 23.7 for the experimental class and 14.99 for the control class. So, this means that the vocabulary skills of seventh grade students at SMPN 3 Parepare have a significant increase. In conclusion, the use of scrabble in training the vocabulary skills of students at SMPN 3 Parepare for the 2020/2021 school year.